A new generation of bioactive dressings for wound-healing management - Souza, Jefferson (2017)
The present work evaluated the surface, thermal, friction, drape and moisture properties of surgical cotton weaved and knitted fabric gauzes coated with chitosan nanocapsules containing essential oil of Copaifera multijuga Hayne. The result indicates that the biofunctionalized medical textiles induce low capillarity, allowing a good degree of moisture and absorption capacity of wound exudates. The gauzes coated with chitosan (CH) at the optimized mass fractions of 0.125 wt% demonstrate good thermal, friction and draping properties, thus promoting the best conditions for maintenance of the wound healing microenvironment. The knitted fabric shows the best thermal, friction and capillarity proprieties compared to weaved gauze. This gauze allows the development of a knitted biofunctionalized medical device especially designed for burn wounds treatment.